THE EFFECTIVENESS OF JIGSAW ON READING COMPREHENSION OF ANALYTICAL EXPOSITION TEXT - Febriana Hidayati; Dedeh Rohayati (Universitas Galuh, 2017)
This paper investigates the effectiveness of Jigsaw on reading comprehension of analytical exposition text. The problems in this research are whether jigsaw has significant difference in reading comprehension of analytical exposition text between students who are taught by using jigsaw learning and those who are taught by using Grammar-Translation Method and how the participants in the experimental group response toward the jigsaw instruction after the treatment. The population of this research was the eleventh grade student of Senior High School in Tasikmalaya in the academic year 2016/2017 consisting of 48 students. The instruments, achievement test used to collect data were pre-test and post-test to experimental and control groups. They served to measure students’ reading comprehension of analytical exposition text by using jigsaw . The instrument, questionnaire was used to collect data about the participants’ response towards using jigsaw in comprehending analytical exposition text. From the research, it could be obtained the t-observed value was 2.410, whereas t-critical was 2.021.It means the alternative hypothesis is accepted and the nul hypothesis is rejected. It can be concluded that there is significant difference in reading comprehension of analytical exposition text between students who are taught by using jigsaw learning and those who are taught by using it. Keywords: Jigsaw , reading comprehension, analytical exposition text